Correlates of Use of Timed Unprotected Intercourse to Reduce Horizontal Transmission Among Ugandan HIV Clients with Fertility Intentions - Wagner, Glenn J.; Goggin, Kathy; Mindry, Deborah; Beyeza-Kashesya, Jolly; Finocchario-Kessler, Sarah; Woldetsadik, Mahlet A.; Khanakwa, Sarah; Wanyenze, Rhoda K. (AIDS and Behavior, 2015)
We examined the correlates of use of safer conception methods (SCM) in a sample of 400 Ugandan HIV clients (75% female; 61% on antiretroviral therapy; 61% with HIV-negative or unknown status partners) in heterosexual relationships with fertility intentions. SCM assessed included timed unprotected intercourse, manual self-insemination, sperm washing, and pre-exposure prophylaxis (PrEP). In the 6 months prior to baseline, 47 (12%) reported using timed unprotected intercourse to reduce risk of HIV infection (or re-infection), none had used manual self-insemination or sperm washing, and 2 had used PrEP. In multiple regression analysis, correlates of use of timed unprotected intercourse included greater perceptions of partner’s willingness to use SCM and providers’ stigma of childbearing among people living with HIV, higher SCM knowledge, and desire for a child within the next 6 months. These findings highlight the need for policy and provider training regarding integration of couples’ safer conception counselling into HIV care.
Keywords: safer conception methods; heterosexual relationships; fertility intentions